2021
DOI: 10.1093/mnras/stab2624
|View full text |Cite
|
Sign up to set email alerts
|

GW Ori: circumtriple rings and planets

Abstract: GW Ori is a hierarchical triple star system with a misaligned circumtriple protoplanetary disc. Recent ALMA observations have identified three dust rings with a prominent gap at $100\, \rm au$ and misalignments between each of the rings. A break in the gas disc may be driven either by the torque from the triple star system or a planet that is massive enough to carve a gap in the disc. Once the disc is broken, the rings nodally precess on different timescales and become misaligned. We investigate the origins of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…( 2) in Facchini et al 2018). In fact, Smallwood et al (2021) carried out smoothed particle hydrodynamics (SPH) simulations with varying viscosities in the disk and found no breaking in the bending-wave regime. They suggest instead that the stellar multiple leads to a warped inner disk after a planet carved a gap in the disk.…”
Section: Observations Of Misaligned Configurationsmentioning
confidence: 99%
“…( 2) in Facchini et al 2018). In fact, Smallwood et al (2021) carried out smoothed particle hydrodynamics (SPH) simulations with varying viscosities in the disk and found no breaking in the bending-wave regime. They suggest instead that the stellar multiple leads to a warped inner disk after a planet carved a gap in the disk.…”
Section: Observations Of Misaligned Configurationsmentioning
confidence: 99%
“…There are two triple star systems that may have planets orbiting them, GG Tauri A (Phuong et al 2020b) and GW Ori (Bi et al 2020;Smallwood et al 2021). The GG Tauri A system consists of three stars (Di Folco et al 2014) with m B = 0.6 M e , m Aa = 0.38 M e , and m Ab = 0.3 M e .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple stellar systems are common in star-forming regions (Duchêne & Kraus 2013). Disks around triple star systems are also expected to be common (Tobin et al 2016;Bate 2018), and there are several well-known examples including GG Tauri A (Di Folco et al 2014;Keppler et al 2020;Phuong et al 2020a) and GW Ori (Bi et al 2020;Kraus et al 2020;Smallwood et al 2021). A common feature of these disks is that they are tilted with respect to the orbital plane of the stars.…”
Section: Introductionmentioning
confidence: 99%
“…The data also indicate complex disk dynamics initiated by the various stellar components. Subsequent work by Smallwood et al (2021) conveyed evidence of disk breaking that, according to the authors, is likely caused by undetected planets, which, if confirmed, would constitute the first planet(s) identified in a circumtriple orbit.…”
Section: Introductionmentioning
confidence: 99%